Tensile properties of plastic concrete and the influence of temperature and cyclic loading. (March 2019) - Combrinck, Riaan; Boshoff, William P.
Abstract: The cracking of plastic concrete remains a problem in the construction industry due to its complexity and incomplete understanding. One of the reasons for this is the lack of knowledge regarding the tensile material properties of the plastic concrete. This paper describes and builds the appropriate test setup needed for the challenging tensile testing of plastic concrete as well as discusses the measured tensile properties. The tensile strength and Young's modulus increase exponentially near the final setting time and initial setting time respectively. The strain capacity and initial fracture energy decrease significantly between the initial and final setting times. The tensile properties develop faster and with higher values the greater the ambient temperature. Plastic concrete proved to be resilient and capable of withstanding multiple loading and ceased loading cycles, while a solid but still weak concrete could not. The tests also highlighted the need for further research regarding the influence of hydrostatic pressure and the relaxation of stresses in plastic concrete.